Rational Speculation - Leach, John (Journal of Political Economy, 1991)
The stationary equilibrium of an overlapping generations economy in which agents trade a single asset is examined. If agents live for only two periods, the selling prices follow an identically and independently distributed process. If agents live for more than two periods, the selling prices follow a Markov process. An implication of the model is that price bubbles can occur in a stationary, rational expectations equilibrium.